Connexin-Related (DFNB1) Hearing Loss: Is Routine Computed Tomography Imaging Necessary?. (May 2015) - Dahl, John P.; Stadler, Michael E.; Huang, Benjamin Y.; Miao, Di; Patel, Mihir R.; Adunka, Oliver F.; Buchman, Craig A.; Fine, Jason P.; Zdanski, Carlton J.
Objectives: Determine if routine computed tomography (CT) imaging is necessary in the workup for children with connexin-related (DFNB1) sensorineural hearing loss (SNHL). Study Design: Case-control retrospective chart and imaging review. Setting: Tertiary care otolaryngology practice. Subjects and Methods: High-resolution temporal bone CT scans of children (n = 21) with DFNB1 SNHL were compared to age-matched controls with either conductive hearing loss (CHL, n = 33) or a nonsyndromic, non-DFNB1 SNHL (n = 33). Sixteen measurements of cochleo-vestibular structures were recorded. Statistical analysis was performed using a repeated analysis of variance model that controlled for both age and gender. Area under the curve (AUC) and multidimensional AUC (MAUC) analyses were also performed. Results: Overall, no statistically significant differences were found between the 3 experimental groups. In addition, comparisons between the DFNB1 and CHL groups, DFNB1 and non-DFNB1 SNHL groups, and CHL and non-DFNB1 SNHL groups failed to demonstrate any statistically significant differences. AUC and MAUC analyses also failed to detect any significant differences between the 3 groups. Conclusions: Patients with DFNB1 SNHL do not have significant anatomic differences on temporal bone CT scans when compared to non-DFNB1 SNHL and CHL control groups. Based on the above analysis, it is reasonable to avoid routine CT imaging of the temporal bones in children with known DFNB1 SNHL unless otherwise clinically indicated.